KAJIAN ELEMEN PEMBENTUK SUASANA RUANG BERTEMA KOREAN STREET VIEW PADA INTERIOR KAFE CHINGU DI BANDUNG - Mahendra Nur Hadiansyah; Dessy Fitrah Ramadhani (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2021)
The role of interior design in creative industry has to accommodate to three goals; function, aesthetic, and visitor’s pyschological state. In a cafe, a designer can be counted as a success if the cafe has a high visitor number and becomes a trend in the local society. One of the café is a popular trend of Korean Theme made famous internationally through the internet and social media in this era of globalization which the Indonesian people exposed to hallyu wave or the Korean fever. Chingu Café located in Bandung that adapts Korean Street View theme to attract visitors who idolize Korean culture. This research aims to determine how the process of interior elements are formed so as to lead the visitor perceptions of Chingu cafe feel the atmosphere themed Korean street view. The method used in this research is qualitative method which include data collecting (via survey), documentation, and group discussion. Based on this research, there are a few elements that attracts visitors; traditional Korean house architecture, interior elements such as mural, signage, neon box, and decorative elements that resembles the elements on Korean streets such as wall with Korean writings, Sakura flower, and vending machines that depict the atmosphere in urban of South Korea. Visitors can feel the thematic atmosphere based on experiences from watching Korean shows or vlog videos traveling in Korea on the internet. Basically, the establishment of an atmosphere of space through the interior elements utilize Chingu café used stereotypes in society about Korea.